Femtosecond laser reduction direct writing ink as well as preparation method and application thereof
Through the preparation method of femtosecond laser reduction direct writing ink, combined with the use of nanoferromagnetic materials, the problem of difficult to prepare metallic patterns of thin film antennas with high conductivity and high magnetic permeability is solved in the prior art, and the weight reduction and production efficiency of thin film antennas are achieved.
Patent Information
- Application Number
- CN202510110228.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing laser reduction direct writing technology is difficult to prepare thin-film antenna metal functional patterns that take into account both high conductivity and high magnetic permeability, and the nanoferromagnetic materials added to the ink have not been effectively utilized.
The preparation method of femtosecond laser reduction direct writing ink is adopted. The ink is prepared by dissolving the metal salt in a mixed solvent of water and a reducing low-carbon alcohol, and heat and stirring, and mixing it with a nanoferromagnetic material to remove water to prepare the ink. This method reduces metal ions to metal element under the action of laser, and optimizes the magnetic permeability through nanoferromagnetic materials.
The magnetic permeability of the metal functional pattern is achieved, the skin depth of electromagnetic waves in the metal layer is reduced, which helps the thin film antenna to reduce weight and improves production efficiency.
Smart Images

Figure CN119799062A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser direct writing, and in particular to a femtosecond laser reduction direct writing ink and a preparation method and application thereof. Background Art
[0002] Antennas are key components of wireless communication systems. Thin-film antennas are a new type of antenna that uses polymer thin-film materials as a substrate and prints or embeds the carrier circuit and electronic components on the film. They have the unique advantages of being light, flexible, and bendable. They are mainly used in modern wireless communications, microwave radio frequency, and millimeter wave communications, such as portable mobile devices, smart wearable devices, and satellite communications. In order to meet different application requirements, the development of softer and lighter thin-film antennas has become an inevitable trend.
[0003] The metal functional pattern on the surface of the thin film antenna usually serves as the working element of the antenna, radiating, receiving and transmitting electromagnetic waves through the current distribution formed by the conductive metal. The conductivity and magnetic permeability of the metal functional pattern jointly determine the skin depth of the antenna working electromagnetic wave on its surface. The smaller the skin depth of the electromagnetic wave on the metal surface, the thinner the thickness required for the electromagnetic wave to penetrate the metal layer, which is more conducive to the preparation of lightweight thin film antennas.
[0004] The existing manufacturing technologies for metal functional patterns of thin-film antennas mainly include patch method, chemical plating and etching method. Compared with the above technologies, laser reduction direct writing technology has better material adaptability and is faster. Laser reduction direct writing technology is a maskless metal pattern manufacturing technology that uses laser energy to reduce high-valent metal ions to metal elements and deposit them along a specified path. It has achieved certain research results in many aspects such as flexible electronics and integrated circuits. The ink involved in the existing laser reduction direct writing technology is mainly composed of metal salts / metal oxides, solvents, reducing agents, and dispersants. The metal pattern formed is mainly composed of metal elements and a small amount of metal oxides. The metal oxides are usually semiconductor materials that are not ferromagnetic. In particular, the oil film used for metal functional patterns that require both high electrical conductivity and high magnetic permeability for thin-film antennas has not yet been involved. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a femtosecond laser reduction direct writing ink and a preparation method and application thereof.
[0006] In a first aspect of the present invention, the present invention provides a method for preparing a femtosecond laser reduction direct writing ink, the method comprising: (1) dissolving a metal salt in a mixed solvent of water and a reducing low-carbon alcohol and heating and stirring to obtain a basic metal salt dispersion; (2) mixing and stirring the basic metal salt dispersion and the nano-ferromagnetic material to obtain a suspension; (3) The suspension is heated to remove water, thereby obtaining a femtosecond laser reduction direct writing ink.
[0007] According to the preparation method of the above-mentioned femtosecond laser reduction direct writing ink provided by the present invention, the metal salt is first dissolved in a mixed solvent of water and a reducing low-carbon alcohol and heated and stirred, and the metal salt and water are fully reacted by heating and stirring to obtain a basic metal salt dispersion. The inventor found that the above-mentioned basic metal salt dispersion is first generated, and then the ink prepared by it can be laser-written to obtain the metal functional pattern of the thin film antenna. If only the metal salt solution is used to prepare the ink, the metal functional pattern of the thin film antenna cannot be prepared. In addition, by adding a reducing low-carbon alcohol, it has the dual role of a metal salt solvent and a metal ion reducing agent. Under the action of the laser, the reducing low-carbon alcohol reduces the metal ions to a metal element and volatilizes and removes them, thereby avoiding a negative impact on the conductivity of the metal pattern. Then the basic metal salt dispersion and the nano-ferromagnetic material are mixed and stirred to uniformly disperse the nano-material. After stirring for a period of time, a uniformly dispersed suspension is obtained. By adding the nano-ferromagnetic material, the magnetic permeability of the metal functional pattern can be optimized and the skin depth of the electromagnetic wave in the metal layer can be reduced. Finally, the suspension obtained above is heated to remove water, thereby obtaining a femtosecond laser reduction direct writing ink.
[0008] According to the preparation method of the femtosecond laser reduction direct writing ink provided by the present invention, in step (1), the volume ratio of the water to the reducing low-carbon alcohol is 1: (3-6). Controlling the volume ratio of water to the reducing low-carbon alcohol within the above range can ensure the reducing ability of the material system, while effectively dissolving the metal salt and maintaining the diffusion ability of the metal ions.
[0009] According to the preparation method of femtosecond laser reduction direct writing ink provided by the present invention, in step (1), the mass ratio of the water to the metal salt is 1: (1-10). Controlling the mass ratio of water to the metal salt within the above range can effectively dissolve the metal salt, release the metal ions into the solution to participate in the reaction, and avoid the metal ions being unable to nucleate due to too low concentration, or the metal salt being incompletely dissolved due to insufficient solvent.
[0010] According to the method for preparing femtosecond laser reduction direct writing ink provided by the present invention, the reducing low-carbon alcohol is selected from one or more of methanol, ethylene glycol, propylene glycol, and glycerol.
[0011] According to the preparation method of femtosecond laser reduction direct writing ink provided by the present invention, the metal salt is selected from one of cupric chloride, cupric nitrate, cupric formate, nickel chloride, nickel nitrate and nickel formate.
[0012] According to the method for preparing a femtosecond laser reduction direct writing ink provided by the present invention, in step (1), the heating temperature is 110-180°C, and the heating time is 10 min-2 h. By controlling the heating temperature and time within the above range, it is possible to ensure that the metal salt and water undergo a sufficient hydrolysis reaction to obtain a uniform basic metal salt dispersion.
[0013] According to the preparation method of femtosecond laser reduction direct writing ink provided by the present invention, in step (2), the nano ferromagnetic material is selected from one of iron, nickel, cobalt, iron-nickel alloy, spinel ferrite, ferric oxide, ferroferric oxide, and cobalt oxide, preferably ferroferric oxide or spinel ferrite. The inventors have found that the use of the above-mentioned nano ferromagnetic materials can significantly optimize the magnetic permeability of the metal functional pattern and effectively reduce the skin depth of the electromagnetic wave in the metal layer.
[0014] In some embodiments of the present invention, the diameter of the nano ferromagnetic material is 20nm-100nm. For example, the diameter of the nano ferromagnetic material is 20nm, 40nm, 60nm, 80nm, 100nm, etc., or the range between any two of the above values. The inventors have found that controlling the diameter of the nano ferromagnetic material within the above range can achieve uniform dispersion of the nano material, avoiding excessive surface energy of the nano material to produce serious agglomeration or excessive density to produce precipitation. It should be noted that the shape of the nano ferromagnetic material is a granular form, similar to a spherical shape, and the diameter of the maximum contour approximating the spherical shape is used to represent the size of the nano ferromagnetic material.
[0015] According to the preparation method of femtosecond laser reduction direct writing ink provided by the present invention, in step (2), the mass ratio of the nano ferromagnetic material to the metal salt is 1: (1-100). For example, the mass ratio of the nano ferromagnetic material to the metal salt is 1: 1, 1: 5, 1: 10, 1: 20, 1: 30, 1: 40, 1: 80, 1: 100, etc., or the range between any two of the above values. The inventors have found that controlling the mass ratio of the nano ferromagnetic material to the metal salt within the above range can improve the magnetic permeability of the metal functional pattern, while avoiding excessive content of the nano material to reduce the electrical conductivity of the metal functional pattern.
[0016] According to the method for preparing femtosecond laser reduction direct writing ink provided by the present invention, in step (2), the stirring includes ultrasonic stirring, magnetic stirring or mechanical stirring, and the stirring time is preferably 2h-4h. By optimizing the stirring method and time, the nanomaterials are evenly dispersed, and the agglomeration and precipitation after the metal ions react with water to form basic salts are avoided.
[0017] According to the method for preparing femtosecond laser reduction direct writing ink provided by the present invention, in step (3), the heating temperature is 70-120°C, and the heating time is 12 h-24 h. The heating temperature and time are controlled within the above range to effectively remove excess water in the ink.
[0018] In a second aspect of the present invention, a femtosecond laser reduction direct writing ink is provided, and the ink is prepared by the above method. Thus, the femtosecond laser reduction direct writing ink can improve the magnetic permeability of the metal functional pattern, reduce the skin depth of the electromagnetic wave in the metal layer, and help reduce the weight of the thin film antenna.
[0019] In some embodiments of the present invention, the ink viscosity is not less than 700 mP∙s.
[0020] In some embodiments of the present invention, the pH value of the ink is weakly acidic, preferably with a pH of 3-4.
[0021] In a third aspect of the present invention, the present invention proposes the use of the above-mentioned femtosecond laser reduction direct writing ink in preparing a metal functional pattern on the surface of a thin film antenna. The present invention utilizes femtosecond laser reduction direct writing of a metal functional pattern to avoid reoxidation of the reduced metal caused by excessive heat effects of a long pulse width or continuous laser, thereby reducing the impact on the conductivity of the metal pattern.
[0022] According to the application of the femtosecond laser reduction direct writing ink provided by the present invention in preparing the metal functional pattern on the surface of the thin film antenna, the femtosecond laser preparation process of the metal functional pattern on the surface of the thin film antenna includes: using a femtosecond laser equipped with a scanning galvanometer system, the laser pulse width is 10 -15 -10 -12 s, laser wavelength is 500-1100 nm, pulse repetition frequency is 100 kHz-1 MHz, laser average power is 1-8 W, spot diameter is 10-300 μm, and spot moving speed is 1-500 mm / s.
[0023] In some embodiments of the present invention, ink is scraped onto the surface of a flexible film to form a film, and then a femtosecond laser is used to restore the metal functional pattern. The scraping method includes one of spin coating, scraping, and drip coating; and the flexible film includes one of polyimide, polyethylene terephthalate, and polycarbonate.
[0024] The present invention at least includes the following technical effects: (1) The present invention adds nano-ferromagnetic materials to the ink, which can optimize the magnetic permeability of the metal functional pattern, reduce the skin depth of electromagnetic waves in the metal layer, and help reduce the weight of the thin film antenna.
[0025] (2) The present invention uses low-carbon polyols in the ink preparation process, which have the dual functions of metal salt solvent and metal ion reducing agent. Under the action of laser, metal ions are reduced to metal elements and volatilized and removed, thereby avoiding negative impact on the conductivity of the metal pattern and helping to achieve weight reduction of the thin film antenna.
[0026] (3) In the ink preparation process of the present invention, the metal salt ions and water are firstly subjected to a sufficient hydrolysis reaction under the action of heating and stirring to obtain a basic metal salt. Agglomeration and precipitation of the basic metal salt are prevented by stirring, thereby effectively realizing the manufacture of the metal functional pattern of the thin film antenna, greatly shortening the reaction time and improving the production efficiency.
[0027] (4) The preparation process of the ink of the present invention is simple and efficient, does not require special protective gas protection, and has low manufacturing cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is a physical picture of the ink prepared in Example 1 of the present invention; Figure 2 This is a physical picture of the femtosecond laser reduction direct writing metal pattern obtained in Example 1 of the present invention; Figure 3 This is a real picture of the ink prepared in Example 2 of the present invention; Figure 4 is a relative dielectric constant diagram of a metal pattern obtained by measurement and calculation in Example 2 of the present invention; Figure 5 This is a relative magnetic permeability diagram of the metal pattern obtained through measurement and calculation in Example 2 of the present invention. DETAILED DESCRIPTION
[0030] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0031] Example 1 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) Weigh 50 mg of ferroferric oxide (diameter 80-100 nm) and add it to the basic copper nitrate dispersion. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (4) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (5) Scrape the ink onto the surface of the polyimide film to form a uniform film; (6) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce the copper ion ink and directly write the metal copper pattern. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 30 mm / s. After processing, the excess metal ion film was rinsed off with deionized water and ethanol, and then dried with compressed air.
[0032] in, Figure 1 This is a physical picture of the copper ion ink obtained in Example 1; Figure 2 This is a real picture of the metal pattern obtained after femtosecond laser reduction direct writing in Example 1. The conductivity of the metal functional pattern after measurement is 4.5×10 4 S / m.
[0033] Example 2 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) Weigh 50 mg of spinel ferrite (diameter 40-50 nm) and add it to the basic copper nitrate dispersion. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (4) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (5) Scrape the ink onto the surface of the polyethylene terephthalate film to form a uniform film; (6) A femtosecond laser with a wavelength of 515 nm, a pulse width of 100 fs, and a repetition rate of 600 kHz was used to reduce the copper ion ink and directly write the metal copper pattern. The laser power was 3 W, the spot diameter was 40 μm, and the scanning speed was 20 mm / s. After processing, the excess metal ion film was rinsed off with deionized water and ethanol respectively, and then dried with compressed air.
[0034] in, Figure 3 This is a physical picture of the copper ion ink obtained in Example 2; Figure 4 The relative dielectric constant of the metal pattern is obtained by measuring and calculating in Example 2; Figure 5 is the relative magnetic permeability of the metal pattern obtained by measurement and calculation in Example 2. Figure 4 It can be seen that when the incident electromagnetic wave frequency is less than 6 GHz, the real part of the relative dielectric constant of the metal pattern can reach below -20. As the electromagnetic wave frequency increases, the relative dielectric constant approaches 0, indicating that in the low-frequency region, the metal pattern can store more electric field energy, reduce electromagnetic wave reflection, and increase wave absorption performance. In the high-frequency region, it is insensitive to frequency and has more stable performance in a wide bandwidth. Figure 5 It can be seen that when the electromagnetic wave frequency band is 2-3 GHz, the real part of the relative magnetic permeability of the metal pattern reaches 2-3, indicating that the metal pattern exhibits significant magnetic loss, which helps to optimize the impedance matching. For high-frequency electromagnetic waves, the real part of the magnetic permeability gradually decreases and approaches 1, showing lower magnetic loss and is not affected by the relaxation effect. Figure 4-5 It shows that the metal pattern manufactured in Example 2 can be selected according to the antenna application scenario and electromagnetic wave frequency band, such as a miniaturized antenna, a low-frequency communication antenna, a high-frequency communication (5G) antenna, etc.
[0035] Comparative Example 1 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) heating the copper ion solution to 170° C. for 25 min, until bubbles are generated in the solution and yellow-brown gas is released, cooling the solution to room temperature to obtain a basic copper nitrate dispersion; (3) placing the basic copper nitrate dispersion on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (4) Scrape the ink onto the surface of the polyethylene terephthalate film to form a uniform film; (5) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce the copper ion ink and directly write the metal copper pattern. The laser power was 3.5 W, the spot diameter was 40 μm, and the scanning speed was 30 mm / s. After processing, the excess metal ion film was rinsed off with deionized water and ethanol, and then dried with compressed air.
[0036] Due to the lack of ferromagnetic nanomaterials in the ink, the femtosecond laser processing area lacks non-uniform nucleation sites for metal atoms. At the same time, compared with the ink containing nanomaterials, the main substance that absorbs laser energy in the ink in Comparative Example 1 is metal ions, which leads to too high penetration depth of the light beam in the ink, too dispersed laser energy, and unable to meet the temperature required for metal ion reduction. Therefore, the ink used in Comparative Example 1 cannot form a metal pattern.
[0037] Comparative Example 2 (1) Measure 6 mL of ethylene glycol and 1.5 mL of deionized water and mix them evenly as a mixed solvent. Weigh 4 g of copper nitrate and add it to the mixed solvent to completely dissolve it to obtain a copper ion solution. (2) Weigh 50 mg of ferroferric oxide (diameter 40-50 nm) and add it to the copper ion solution. Place the mixed liquid in an ultrasonic oscillator with a frequency of 40 kHz and oscillate for 2 h to obtain a uniformly dispersed suspension. (3) placing the suspension on a magnetic stirring platform with a heating function, setting the temperature to 120°C, setting the magnetic speed to 1000 r / min, and heating for 12 h to finally obtain copper ion ink; (4) Scrape the ink onto the surface of the polyethylene terephthalate film to form a uniform film; (5) A femtosecond laser with a wavelength of 1030 nm, a pulse width of 100 fs, and a repetition rate of 100 kHz was used to reduce the copper ion ink and directly write the metal copper pattern. The laser power was 3 W, the spot diameter was 40 μm, and the scanning speed was 20 mm / s. After processing, the excess metal ion film was rinsed off with deionized water and ethanol, and then dried with compressed air.
[0038] Since the important steps of heating and stirring to prepare the basic copper dispersion are missing in the ink preparation process, the ink contains acid salts that are completely dissolved in the solvent, and the strong acid radicals have strong oxidizing properties. Compared with strong acid and weak base salts, basic salts are less stable and are more easily decomposed into intermediate products and reduced to metal elements under the action of laser heating and reducing solvents. Therefore, the ink used in Comparative Example 2 also cannot prepare a metallic copper pattern.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a femtosecond laser reduction direct writing ink, characterized in that: include: (1) dissolving a metal salt in a mixed solvent of water and a reducing low-carbon alcohol and heating and stirring to obtain a basic metal salt dispersion; (2) mixing and stirring the basic metal salt dispersion and the nano-ferromagnetic material to obtain a suspension; (3) The suspension is heated to remove water, thereby obtaining a femtosecond laser reduction direct writing ink.
2. The method according to claim 1, characterized in that: In step (1), the volume ratio of the water to the reducing low-carbon alcohol is 1:(3-6); And / or, the mass ratio of the water to the metal salt is 1:(1-10).
3. The method according to claim 1 or 2, characterized in that: The reducing low-carbon alcohol is selected from one or more of methanol, ethylene glycol, propylene glycol, and glycerol; And / or, the metal salt is selected from one of cupric chloride, cupric nitrate, cupric formate, nickel chloride, nickel nitrate and nickel formate.
4. The method according to claim 1 or 2, characterized in that: In step (1), the heating temperature is 110-180° C., and the heating time is 10 min-2 h.
5. The method according to claim 1, characterized in that: In step (2), the nano ferromagnetic material is selected from one of iron, nickel, cobalt, iron-nickel alloy, spinel ferrite, ferric oxide, ferroferric oxide, and cobalt oxide, preferably ferroferric oxide or spinel ferrite; And / or, the diameter of the nano ferromagnetic material is 20nm-100nm.
6. The method according to claim 1 or 5, characterized in that: In step (2), the mass ratio of the nano ferromagnetic material to the metal salt is 1:(1-100); And / or, in step (2), the stirring includes ultrasonic stirring, magnetic stirring or mechanical stirring, and preferably the stirring time is 2h-4h.
7. The method according to claim 1, characterized in that: In step (3), the heating temperature is 70-120° C., and the heating time is 12 h to 24 h.
8. A femtosecond laser reduction direct writing ink, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the femtosecond laser reduction direct writing ink according to claim 8 in preparing metal functional patterns on the surface of thin film antennas.
10. The use according to claim 9, characterized in that: The femtosecond laser preparation process of the metal functional pattern on the surface of the thin film antenna includes: using a femtosecond laser equipped with a scanning galvanometer system, with a laser pulse width of 10 -15 -10 -12 s, laser wavelength is 500-1100 nm, pulse repetition frequency is 100 kHz-1 MHz, laser average power is 1-8 W, spot diameter is 10-300 μm, and spot moving speed is 1-500 mm / s.
Citation Information
Patent Citations
Micrometric direct-write methods for patterning conductive material and applications to flat panel display repair
CN101002513A
Method of constructing graphical magnetic micro-nano structure through laser beam direct writing
CN105036057A
Method for manufacturing metal microstructure through high repetition frequency ultrafast laser efficient direct writing
CN112517922A
Ink direct writing preparation method of multilayer gradient wave-absorbing material
CN117402518A
Laser direct writing
US5378508A